Bacterial-Derived Polymer Poly-γ-Glutamic Acid (γ-PGA)-Based Micro/Nanoparticles as a Delivery System for Antimicrobials and Other Biomedical Applications - Khalil, Ibrahim R. (Int J Mol Sci, 2017)
In the past decade, poly-γ-glutamic acid (γ-PGA)-based micro/nanoparticles have garnered remarkable attention as antimicrobial agents and for drug delivery, owing to their controlled and sustained-release properties, low toxicity, as well as biocompatibility with tissue and cells. γ-PGA is a naturally occurring biopolymer produced by several gram-positive bacteria that, due to its biodegradable, non-toxic and non-immunogenic properties, has been used successfully in the medical, food and wastewater industries. Moreover, its carboxylic group on the side chains can offer an attachment point to conjugate antimicrobial and various therapeutic agents, or to chemically modify the solubility of the biopolymer. The unique characteristics of γ-PGA have a promising future for medical and pharmaceutical applications. In the present review, the structure, properties and micro/nanoparticle preparation methods of γ-PGA and its derivatives are covered. Also, we have highlighted the impact of micro/nanoencapsulation or immobilisation of antimicrobial agents and various disease-related drugs on biodegradable γ-PGA micro/nanoparticles.